Reliability Analysis of Social and Emotional Learning Measures (Journal of Organizational Psychology, 2021)
The current study examines the score reliability of survey measures of social and emotional learning constructs. In accordance with the Standards for Educational and Psychological Testing, this study collects validity evidence based on internal structure by conducting a confirmatory factor analysis to estimate reliability with coefficient hierarchical omega. This provides one estimate for the multidimensional construct of social and emotional learning and estimates for each subscale.
Keywords: organizational psychology; social and emotional learning; survey; psychometric; reliability; alpha; omega